Machaon CVE: Cluster validation for gene expression data - Bolshakova, Nadia; Azuaje, Francisco (Trinity College Dublin, Department of Computer Science, 2003)
This paper presents a cluster validation tool for gene expression data. Machaon-CVE (Clustering and Validation Environment) system aims to partition samples or genes into groups characterised by similar expression patterns, and to evaluate the quality of the clusters obtained.
Keywords: Computer Science